Pengembangan Perangkat Pembelajaran Himpunan dengan Model Problem Based Learning Berorientasi Pendidikan Karakter untuk Meningkatkan Kemampuan Pemecahan Masalah - Ni Wayan Mei Ekayanti; I Nengah Suparta; I Gusti Putu Sudiarta (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aimed to know the characteristics of the device and the results development of set learning device with Problem Based Learning models oriented character education that was quality is valid, practical and effective. In this study developed learning tools in the form of Teacher Book and Student Books. The type of research used is design research. The subjects of this study were students of Denpasar State Middle School Saraswati 1. The Development of the learning tool follows the Plomp development procedure which includes the preliminary phases, prototype phase, and assessment phase. The learning device validity data was based on expert opinion. The practicality data of instructional devices is based on instruction learning device data, student response questionnaire and teacher response questionnaire. Data on the effectiveness of instructional tools were collected using mathematical problem-solving tests. The validation results indicated that the teacher book and the student books manuals developed obtained valid categories. The results of observation of the implementation of learning, repons students and teacher responses indicate that the implementation of learning was categorized as practical. Based on the results of the test the learning device was included in the effective criteria.